An Overview of Colonization of Supply Chain and its Ugly Smile - Deif, Ahmed; Bergener, Audrey (International Journal of Supply Chain and Logistics, 2025)
Purpose: This paper reframes contemporary supply‑chain “best practices” through a decolonial lens. It explains how value capture mechanisms—offshoring, arm’s‑length contracting, intellectual‑property (IP) control, and audit‑led compliance—reproduce colonial power asymmetries and produce the ‘Ugly Smile’ in value distribution across global value chains. Methodology: Conceptual–analytical synthesis of historical and contemporary literatures on colonialism, global value chains (GVCs), and social sustainability; brief scoping of supply‑chain/operations scholarship; illustrative case logic on consumer electronics (Apple iPhone) to exemplify value allocation patterns. Findings: Interacting modes—unequal exchange, labor arbitrage with arm’s‑length contracting, IP‑centric control, compliance cascades, and raw‑materials extraction—systematically depress midstream capture while concentrating rents upstream (design/IP) and downstream (branding/retail). Recent governance shifts (e.g., EU Corporate Sustainability Due Diligence Directive) move firms beyond tier‑1 audits toward risk‑based responsibility and access to remedy. Unique Contribution to Theory, Practice and Policy: Proposes a consolidated frame that links ‘Ugly Smile’ value distribution to identifiable institutional mechanisms; articulates a forward agenda combining value re‑allocation, worker‑voice governance, longer‑term contracting, open‑licence technology, incentive‑compatible public procurement, and fair‑value metrics to operationalize decolonization in supply chains.